Mid-term outcome of volar plate fixation for scaphoid nonunion. (1st December 2020) - Schormans, Philip Marcel Jozef; Kooijman, Maria A.; Ten Bosch, Jan A.; Poeze, Martijn; Hannemann, Pascal F. W.
Abstract : Aims: Fixation of scaphoid nonunion with a volar locking plate and cancellous bone grafting has been shown to be a successful technique in small series. Few mid- or long-term follow-up studies have been reported. The aim of this study was to report the mid-term radiological and functional outcome of plate fixation for scaphoid nonunion. Methods: Patients with a scaphoid nonunion were prospectively enrolled and treated with open reduction using a volar approach, debridement of the nonunion, and fixation using a locking plate and cancellous bone grafting, from the ipsilateral iliac crest. Follow-up included examination, functional assessment using the patient-rated wrist/hand evaluation (PRWHE), and multiplanar reformation CT scans at three-month intervals until union was confirmed. Results: A total of 49 patients with a mean age of 31 years (16 to 74) and a mean duration of nonunion of 3.6 years (0.4 to 16) were included. Postoperatively, the nonunion healed in 47 patients (96%) as shown on CT scans. The mean time to union was 4.2 months (3 to 12). Due to impingement of the plate on the volar rim of the radius and functional limitation, the hardware was removed in 18 patients. At a median follow-up of 38 months in 34 patients, the mean active range of motion (ROM) improved significantly from 89° to 124° (SD 44°; p = 0.003). The mean grip strength improved significantly from 52% to 79% (SD 28%; p < 0.001) of the contralateral side. The mean PRWHE score improved significantly from 66 to 17 points (SD 25; p < 0.001). Conclusion: Locking plate fixation supplemented with autologous cancellous bone grafting is a successful form of treatment for scaphoid nonunion. Functional outcomes improve with the passage of time, and mid-term results are excellent with a significant improvement in ROM, grip strength, and functional outcome as measured by the PRWHE. Cite this article: Bone Joint J 2020;102-B(12):1697–1702.